CORRELATION BETWEEN SKIN MICROBIAL INFECTION AND IgE, LPS IN SERUM WITH ATOPIC DERMATITIS - M., Zina; AlAubydi, M. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to find the most prevalent microbial isolates, as well as measurement of total serum IgE, LPS levels and their correlation with Atopic dermatitis occurrences. A 88 patients were collected randomly (47 females and 41 males), through a period Sep. 2019 to Feb. 2020 from Al Zafaraniyah General Hospital. Patients ages ranged between 10 months to 30 years. In addition, the control samples are collected randomly from 20 apparently healthy people. Microbial isolation results showed that the most prevalence microbial isolates in atopic skin patients were; Staphylococcus spp. 81 (30.10%), fungi 65 (24.20%), Bacillus spp. 53 (19.70%), Enterobacteriaceae spp. 32 (11.90%), Acinetobacter spp. 16 (5.90%), Corynobacterium spp. 10 (3.70%), Streptococcus spp. 8(3.00%) and Pseudomonas spp. 4 (1.50%) compared with control group. Antimicrobial susceptibility test was carried out for nine antimicrobial agents. The results showed that, most bacterial isolates are become a multidrug resistant especially Staphylococcus spp. and Enterobacteriaceae spp. whilst two other tests in a concern with the AD patients which are IgE and LPS, both parameters results show that, the age from 0 - 2 years, is recorded higher serum level than other age categories.